The Effect of Maternal Body Composition and Triglyceride Levels on Newborn Weight in Non-Diabetic Women with Positive Diabetic Screens - Cüneyt Eftal Taner; Seçil Kurtulmuş; Ümit Nayki; Ayşen Kızılyar; Yasemin Baskın (Medical Network, 2008)
OBJECTIVE: To determine the effect of maternal body composition and triglyceride levels on newborn weight in nondiabetic women with positive diabetic screening. STUDY DESIGN : 40 pregnant women with positive diabetic screenings and negative glucose tolerance tests were enrolled as the study group. 72 pregnant women with negative diabetic screenings were enrolled as the control group. 50-gram glucose challenge tests were performed at 24-32 weeks of gestations and serum lipid levels were measured. The association between maternal serum triglyceride (TG) levels, maternal pre-pregnant body mass index (BMI), maternal weight gain during pregnancy and newborn weight in both groups were compared. RESULTS: The incidence of the infants with >75 percentile newborn weight and the incidence of maternal hypertriglyceridemia were significantly higher in the study group (p<0.05). In this group maternal weight gain during pregnancy was significantly correlated with newborn weight and mean serum triglyceride levels were higher than the control group (p<0.05). CONCLUSION: In non-diabetic pregnant women with positive diabetic screens maternal weight gain during pregnancy was significantly correlated with newborn weight and incidences of infants with >75 percentile newborn weights were significantly higher than control group.